2017
DOI: 10.1111/gtc.12464
|View full text |Cite
|
Sign up to set email alerts
|

Immature Core protein of hepatitis C virus induces an unfolded protein response through inhibition of ERAD‐L in a yeast model system

Abstract: The structural protein Core of hepatitis C virus (HCV), a cytosolic protein, induces endoplasmic reticulum (ER) stress and unfolded protein response (UPR) in hepatocytes, and is responsible for the pathogenesis of persistent HCV infection. Using yeast as a model system, we evaluated mechanisms underlying Core-induced interference of ER homeostasis and UPR, and found that UPR is induced by the immature Core (aa 1-191, Core191) but not by the mature Core (aa 1-177, Core177). Interestingly, Core191 inhibits both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…On the other hand, HCV mature core 177 (aa 1-177) inhibited only ERAD-M and not ERAD-L. Hence, Takashi and colleagues suggested that HCV core 191 may play a role in the induction of UPR in yeast by inhibiting ERAD-L (Takahashi et al 2017).…”
Section: Rna Virusesmentioning
confidence: 99%
“…On the other hand, HCV mature core 177 (aa 1-177) inhibited only ERAD-M and not ERAD-L. Hence, Takashi and colleagues suggested that HCV core 191 may play a role in the induction of UPR in yeast by inhibiting ERAD-L (Takahashi et al 2017).…”
Section: Rna Virusesmentioning
confidence: 99%
“…The most intensively investigated example is the Hepatitis C virus (HCV) core protein which is required for subsequent assembly of viral particles at lipid droplets and therefore finally also virus production and propagation [ 98 101 ]. Loss of SPP leads to an impaired maturation of the HCV core protein and the subsequent TRC8-dependent degradation of the immature precursor through the ERAD pathway [ 102 , 103 ]. Due to its essential role in the viral life cycle, pharmacological inhibition of SPP can suppress HCV replication in cultured cells [ 104 ].…”
Section: Pathophysiological Functions Of Spp/sppl Proteasesmentioning
confidence: 99%
“…These UPR transducers are kept inactive by binding to the ER chaperone GRP78/BiP (the master regulator of UPR) when the ER folding capacity is operating normally. Activators of UPR either cause the ER stress through depletion of Ca 2+ from the ER (14), or the accumulation of unfolded/misfolded, overexpressed or modified proteins in the ER, any of which dissociates the UPR transducers from BiP to activate UPR signaling (15, 16). …”
Section: Introductionmentioning
confidence: 99%
“…Mechanistically, Shiga toxigenic strains of Escherichia coli produce AB5 subtilase cytotoxin that binds to and inactivates BiP to activate the UPR transducers (20); Hepatitis C virus activates UPR at least in part due to the accumulation of immature core protein (Core 199) in the ER lumen (15), while L. monocytogenes require its cholesterol-dependent cytolysin toxin (listeriolysin O) to induce UPR (18). However, the mechanism of UPR activation by Chlamydia is not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation